AN ANALYSIS OF COOPERATIVE PRINCIPLE MAXIMS IN THE MAIN CHARACTER’S DIALOGUES IN THE HEAT MOVIE - Raneta Oktaviyah Mahfudz; Nurlaila Nurlaila (UG Journal, 2022)
According to Grice's cooperative principle (1975), speakers must obey cooperative principles maxims to provide the required information. However, speakers also flout maxims for several reasons, such as incapability of speaking briefly, honestly, clearly, and relevantly. This research aims to find out the kinds of cooperative principle maxims obeyed and flouted by the main character in The Heat movie. The researcher uses a descriptive qualitative method. The data of this research are Mullins’ dialogue as the main character. The data source is The Heat movie. The results of this research show that 49 out of 89 data obey cooperative principle maxims, including the maxim of quality (32), the maxim of relation (9), the maxim of manner (4), and the maxim of quantity (4). Besides that, 40 out of 89 data flout cooperative principles maxims, including flouting the maxim of relation (16), the maxim of quantity (12), the maxim of manner (9), and the maxim of quality (3). The conclusion is that the main character in The Heat movie tends to obey the maxim of quantity and flout the maxim of relation.